Pendampingan Pembuatan Web Profil Perusahaan Sebagai Media Promosi Pada PT. Ratakan Media Kreasi - Sandradewi, Kumaratih; Ahyar, Khoirul; Retno Wahyu Utami, Yustina; Ady Prabowo, Iwan; Irawati, Tri; Remawati, Dwi (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
The digitalization of business has increasingly become an urgent need, especially in efforts to expand marketing reach and enhance consumer trust. PT. Ratakan Media Kreasi, as a company engaged in digital marketing, requires an online platform capable of displaying the company profile professionally and accessibly. This community service activity aims to design and develop a company profile website that can function as a promotional medium and a means of communication with potential clients and business partners. This website is expected to continuously support PT. Ratakan Media Kreasi in achieving digital marketing objectives and sustainably increasing its online presence. This community service activity provides long-term benefits for the company in facing competition in a dynamic digital era.